2016
DOI: 10.1017/jfm.2016.419
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional instabilities and inertial waves in a rapidly rotating split-cylinder flow

Abstract: The nonlinear dynamics of the flow in a differentially rotating split cylinder is investigated numerically. The differential rotation, with the top half of the cylinder rotating faster than the bottom half, establishes a basic state consisting of a bulk flow that is essentially in solid-body rotation at the mean rotation rate of the cylinder and boundary layers where the bulk flow adjusts to the differential rotation of the cylinder halves, which drives a strong meridional flow. There are Ekman-like layers on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…In this second case, the boundary layer of the bases (Ekman type) and the boundary layer of the cylindrical wall (Stewartson type) [25] meet on the corners and an instability in the form of periodic or quasiperiodic states can appear and propagate from the faster corner to the slower corner depending on the Ro according to Refs. [23,28]. Hence, the zone near the cylindrical wall has to adapt its angular velocity from the solid-body rotation ( ) to the wall rotation ( ± ω).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this second case, the boundary layer of the bases (Ekman type) and the boundary layer of the cylindrical wall (Stewartson type) [25] meet on the corners and an instability in the form of periodic or quasiperiodic states can appear and propagate from the faster corner to the slower corner depending on the Ro according to Refs. [23,28]. Hence, the zone near the cylindrical wall has to adapt its angular velocity from the solid-body rotation ( ) to the wall rotation ( ± ω).…”
Section: Resultsmentioning
confidence: 99%
“…Gutierrez-Castillo and Lopez [28] reproduced this analysis numerically in two dimensions (axisymmetric flows) and extended it for large but finite rotation velocities (nonlinear viscous problem) and larger differential rotations studying the stability of the main flow. Later this numerical analysis was extended in three dimensions [23] finding nonaxisymmetric instabilities. For this corotating split cylinder, the flow developed inside is in almost solid-body rotation at the average rotation rate, as in the Stewartson's problem, and a meridional flow appears driving fluid from one end wall to the other with the sandwich structure found in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in [23], when the flow is not restricted to being axisymmetric, [22] have shown that the primary instabilities are three-dimensional. Depending on ω 0 and δω, rotating waves localised in the junction region of the slower rotating half of the cylinder are found, either with low or high azimuthal wave numbers.…”
Section: Steady Differential Rotationmentioning
confidence: 93%
“…However, the associated wave beams are not evident in the nonlinear solutions. High wave number beam do not penetrate deep into the interior [44,22], and so even if there is turbulence in the boundary layers (broad-band spatial spectrum), only the low wave number part of the spectrum drives beams into the interior. So, the interior remains laminar and coherent with low wave number shear layers.…”
Section: Steady Differential Rotationmentioning
confidence: 99%